Biomechanical modeling and computer simulation of the brain during neurosurgery. (5th September 2019) - Miller, Karol; Joldes, Grand R.; Bourantas, George; Warfield, Simon K.; Hyde, Damon E.; Kikinis, Ron; Wittek, Adam
Abstract: Computational biomechanics of the brain for neurosurgery is an emerging area of research recently gaining in importance and practical applications. This review paper presents the contributions of the Intelligent Systems for Medicine Laboratory and its collaborators to this field, discussing the modeling approaches adopted and the methods developed for obtaining the numerical solutions. We adopt a physics‐based modeling approach and describe the brain deformation in mechanical terms (such as displacements, strains, and stresses), which can be computed using a biomechanical model, by solving a continuum mechanics problem. We present our modeling approaches related to geometry creation, boundary conditions, loading, and material properties. From the point of view of solution methods, we advocate the use of fully nonlinear modeling approaches, capable of capturing very large deformations and nonlinear material behavior. We discuss finite element and meshless domain discretization, the use of the total Lagrangian formulation of continuum mechanics, and explicit time integration for solving both time‐accurate and steady‐state problems. We present the methods developed for handling contacts and for warping 3D medical images using the results of our simulations. We present two examples to showcase these methods: brain shift estimation for image registration and brain deformation computation for neuronavigation in epilepsy treatment. Abstract : 1) Fully nonlinear (accounting for large deformations and nonlinear material behavior) procedures of computational mechanics are recommended for biomechanical modeling of the brain during neurosurgery.2) Explicit time integration is well suited for parallel implementation (including implementation on graphics processing units GPUs) and facilitates efficient solution of both time‐accurate and steady state problems in biomechanical modeling and simulation of the brain.3) Application of nonlinear finite element and meshless procedures in brain shift estimation for image registration and brain deformation computation for neuro navigation in epilepsy treatment indicates that, if Dirichlet‐type boundary conditions are used, accurate prediction of the brain deformations can be achieved without patient‐specific information about the brain tissue material properties.